Islamic modernism and the re-enchantment of the sacred in the age of history - Ringer, Monica M., 1965- (Edinburgh University Press, 2020)
This book studies the complex relationship of religion to modernity and argues that modernity should be understood as the consequence, not the cause, of the new intellectual landscape of the 19th century. Shows how the adoption of historicism in the 19th century engendered Islamic modernism as a theological reform movement.